Ciencia, Tecnología y Derecho Ambiental - Verna Coronado, Vito Leonardo (2021)
The article intends to be the beginning of the exploration of the dynamics that take place between science, technology and Environmental Law, starting from the explanation of the characteristics of Environmental Law and confronting them with a vision of science and technology that is perhaps somewhat anachronistic in light of what technology implies for the human species nowadays. It is therefore only an invitation to investigate.